1992
DOI: 10.1016/0014-5793(92)80386-u
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinase‐2 (TIMP‐2) has erythroid‐potentiating activity

Abstract: Tissue inhibitor of metalloproteinase (TIMP) was purified and molecularly cloned on the basis of its erythroid.potentiating activity (EPA). TIMP/EPA appears to be a bifunctional molecule with both growth factor and anti-enzymatic activity. Recently, a ~g~ond TINlP-relatcd molecule was identified and we have investigated its possible erythroid-lmtentiating activity. Native, purified human TIMP-2 was assayed for erythroid. potentiating activity using an in vitro erythroid burst formation assay and was compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(133 citation statements)
references
References 41 publications
3
128
0
2
Order By: Relevance
“…Like TIMP-1, TIMP-2 promotes cell growth in culture (Hayakawa et al, 1994;Nemeth et al, 1996;Stetler-Stevenson et al, 1992) and appears to inhibit tumor growth in vivo (Imren et al, 1996). Although some studies indicate that TIMP-2 expression tends to be similar in tumors and matched normal tissues (Stetler-Stevenson et al, 1990), others have found a signi®cant correlation between TIMP-2 expression and the development of distant metastases (Ree et al, 1997).…”
Section: Timps May Promote and Suppress Carcinogenesis By Distinct Mementioning
confidence: 99%
“…Like TIMP-1, TIMP-2 promotes cell growth in culture (Hayakawa et al, 1994;Nemeth et al, 1996;Stetler-Stevenson et al, 1992) and appears to inhibit tumor growth in vivo (Imren et al, 1996). Although some studies indicate that TIMP-2 expression tends to be similar in tumors and matched normal tissues (Stetler-Stevenson et al, 1990), others have found a signi®cant correlation between TIMP-2 expression and the development of distant metastases (Ree et al, 1997).…”
Section: Timps May Promote and Suppress Carcinogenesis By Distinct Mementioning
confidence: 99%
“…Many investigators have demonstrated that human and rodent metastatic malignant cells produce larger amounts of MMP-2 than do non-metastatic cells, both in vitro and in vivo (Liotta et al, 1980;. Tissue inhibitor of metalloproteinases-2 (TIMP-2), an unglycosylated protein of 21-kDa molecular weight, strongly inhibits the biological activity of MMP-2, and was shown to strongly inhibit cancer invasion, metastasis, growth and angiogenesis in some rodent and human tumours (Stetler-Stevenson et al, 1989;DeClerck et al, 1992). Therefore, it is likely that an imbalance in the MMP-2 and TIMP-2 ratio plays an important role in cancer invasion, metastasis and angiogenesis DeClerck et al, 1994).…”
mentioning
confidence: 99%
“…There are other reports of such bifunctional molecules. Tissue inhibitor of metalloproteinase is a molecule that has both anti-protease activity and growth-factor activity [32]. PLA # from bovine seminal plasma has been shown to be a platelet-activating factor acetylhydrolase [33].…”
Section: Mechanism Of Action Of Efmentioning
confidence: 99%